(untitled) (Bangladesh Journal of Pharmacology, 2015)
A drimane type sesquiterpenoids, sulphureuine B was isolated from the edible mushroom Laetiporus sulphureus and its antiproliferative properties were investigated using U-87MG glioma cells. It was observed that sulphu-reuine B-induced apoptosis in U-87MG cells and the mechanisms involved are endoplasmic reticulum stress, mitochondrial and death receptor mediated pathways. Endoplasmic reticulum stress was identified from the results of enormous cytoplasmic vacuolation, CHOP elevation and caspase-12 cleavage. Further, we found that treatment of sulphureuine B-induced PERK, IRE1?, and ATF6? activations. In addition, sulphureuine B-induced Bcl-2 down-regulation, cleavage of PARP, and caspase-8 activation were also affected. All these experimental results clearly revealed that sulphureuine B-induced apoptosis mediated through endoplasmic reticulum stress, mitochondrial, and death receptor signaling pathways.